Results of the ECHO (Eating habits CHanges in Oncologic patients) Survey: An Italian Cross-Sectional Multicentric Study to Explore Dietary Changes and Dietary Supplement Use, in Breast Cancer Survivors - Caprara, Greta; Tieri, Maria; Fabi, Alessandra; Guarneri, Valentina; Falci, Cristina; Dieci, Maria Vittoria; Turazza, Monica; Ballardini, Bettina; Bin, Alessandra; Cinieri, Saverio; Vici, Patrizia; Montagna, Emilia; et al. (Frontiers in Oncology, 2021)
The role of a healthy diet in cancer prevention is well recognized. Recent data indicate that following the same advices can also improve cancer survivors’ quality of life. Breast cancer (BC) patients are commonly concerned about diet and nutrition and frequently express the need to obtain health-related information and the will to change their diet and lifestyle. Hence, be aware of survivors’ dietary changes and information needs is crucial for healthcare professionals to guide them toward optimal lifestyle choices. In order to investigate eating habits changes in a BC survivors’ population, we conceived the cross-sectional multicentric study ECHO (Eating habits CHanges in Oncologic patients) SURVEY. Data were collected from 684 patients, diagnosed with invasive breast cancer, in order to investigate their changes in food consumption, use of supplements, or the beginning of a specific diets, after BC diagnosis. We also examined the sources of information used and if any modification in their diets was reported to the oncologist. We primarily observed that patients increased their consumption of vegetables, pulses, nuts, fruits, wholemeal bread/pasta, grains and fish; while decreasing red and processed meat, refined bread/pasta, baked good and animal fat consumption. Survivors also reported the use of dietary supplements, mainly vitamins, aimed at counteracting therapies’ side effects. Changes in nutritional habits were often adopted without asking or informing the oncologist. Despite BC survivors made some positive changes in their nutritional habits, those modifications were mostly pursued by less than half of them, while the majority of patients consumed nutritional supplements after diagnosis. These results, as well as the failure to communicate with the physicians, reinforce the need to both improve the patient-healthcare professional relationship and to develop tailored nutrition counselling and intervention programs for cancer survivors.